HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN BURNOUT PADA TENAGA KESEHATAN DI WILAYAH JABODETABEK SELAMA MASA PANDEMI COVID-19 - Dimas Dwi Mulya, (2022)
Burnout is considered as one of the most popular problems today among workers, especially among health workers. The COVID-19 pandemic has increased the working hours of health workers. For health workers, it has an impact on performance and mental condition. Burnout is caused by excessive work demands, causing health workers to be drained of energy and thoughts. Physical activity can be one solution to reduce burnout. This is because physical activity produces certain hormones that help to reduce burnout. Several studies have stated that the current decline in excessive physical activity has led to mental health problems, namely burnout and the most common indication of burnout experienced by health workers is fatigue. The purpose of this study was to determine the relationship between physical activity and the incidence of burnout in health workers. This study uses a quantitative method with a cross-sectional study design using a questionnaire. The parameters used to measure physical activity are GPAQ (Global Physical Activity Questionnaire) and burnout using MBI-HSS (Maslach Burnout Inventory - Human Services Survey). Based on the results of the data obtained in this study, the Speaman test using the SPSS version 25 application was obtained with a p value of 0.000 (<0.05) physical activity with a value of r = 1 and burnout with a value of r = -0,273. The conclusion of physical activity with burnout has a relationship with weak strength.